2019
DOI: 10.1007/s00256-019-03179-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI and ultrasound of the hands and wrists in rheumatoid arthritis. I. Imaging findings

Abstract: The management of patients with rheumatoid arthritis (RA) has rapidly evolved with the development of newer diseasemodifying drugs and the recognition that long-term damage can be mitigated by an earlier and more-informed use of these medications. Historically, radiographs were the mainstay of imaging in RA patients, but radiographic joint narrowing and erosions are late and insensitive findings in the disease. MRI (with intravenous contrast agent) and ultrasound (with power Doppler interrogation) of the hands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 145 publications
1
28
0
2
Order By: Relevance
“…Multiple previous studies have reported clinical and imaging remission in patients with RA, but few studies have focused on functional remission [4,30]. In the present study, we investigated important factors associated with QOL in patients with RA, and our findings suggest that the disease duration, PDQ, PSEQ, PCS, use of oral steroids, and use of oral analgesics play important roles in achieving functional remission.…”
Section: Discussionmentioning
confidence: 73%
“…Multiple previous studies have reported clinical and imaging remission in patients with RA, but few studies have focused on functional remission [4,30]. In the present study, we investigated important factors associated with QOL in patients with RA, and our findings suggest that the disease duration, PDQ, PSEQ, PCS, use of oral steroids, and use of oral analgesics play important roles in achieving functional remission.…”
Section: Discussionmentioning
confidence: 73%
“…However, synovitis of the ACW has been rarely reported [ 29 ]. In our study, 90.1% of patients showed effusion in the joint cavities, although some of the manifestation may be physiological effusions, which should be proved by enhanced MRI [ 30 , 31 ]. In addition, the sternal angle, which is in the vicinity of the second SCoJ (containing an interarticular ligament and two synovial membranes) and contains the manubriosternal joint (containing dorsal and ventral ligaments and classified as a synovial joint in ~ 30% patients [ 20 ]), was the third-most frequently involved site.…”
Section: Discussionmentioning
confidence: 77%
“…Second, the non-contrast-enhanced MRI could not show all the involved veins, such as subclavian veins. The sensitivity and specificity for identifying synovitis and tenosynovitis are also lower using T2-weighted sequences alone compared with contrast-enhanced images [ 30 ]. Third, there was no computed tomography serving as a reference to accurately assess ossification of the costal cartilage and ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…Only the use of contrast-enhanced MRI can make the distinction -the inflamed synovium enhances after contrast injection [26]. However, gadolinium administration raises the cost and duration of the MRI examination and adds considerable discomfort to the patients [29]. It was demonstrated that US and MRI are useful and reliable imaging techniques in identifying tenosynovitis [5,12].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow edema or osteitis (inflammation of the subchondral trabecular bone), findings specific for inflammatory arthropathy, denotes a severe and aggressive disease phenotype, and predicts the structural damage progression of the disease [29,36]. MRI is the only imaging technique capable of visualizing this abnormality.…”
Section: Discussionmentioning
confidence: 99%